Carboxylic acid-protruding zincophosphate sheets exhibiting surface mechanochemical reactivity and intriguing nano-morphological reversibility. Issue 17 (10th January 2019) - Hung, Ling-I; Yi, Hsiang-Yi; Shih, Yu-Chieh; Lin, Chia-Her; Wang, Sue-Lein
Abstract : A hybrid zincophosphate with surface-active and interior –COOH exhibits remarkable characteristics of high thermal stability, modifiable wettability and nano-morphological reversibility. Abstract : For the first time, functional carboxylic acid (–COOH) groups protruding on both sides of zincophosphate sheets are prepared, leading to a unique surface-active lamellar material characterized by modifiable wettability via a facile mechanochemical reaction. The interior –COOH groups lead to high thermal stability unusual to hybrid-layer structures and undergo the intriguingly reversible nano-morphological transformation never unveiled in metal oxysalts before.